Putnički brodovi za krstarenje - JVOVIĆ, Jovo (Promet - Traffic&Transportation, 2026)
PASSENGER CRUISING VESSELS The paper first deals with a review of the fleet of vessels for cruises in the world, building and order status, and evaluates the trends of this specific travel phenomenon in conjunction with the identification of major world cruising regions. Brief mention has been made of the capacity of the Yugoslav passenger fleet and building of passenger vessels in our shipyards. The author concludes that the sea cruises industry will maintain high growth rates.